Grand Challenges in Immersive Analytics. - Ens, Barrett.; Bach, Benjamin.; Cordeil, Maxime.; Engelke, Ulrich.; Serrano, Marcos.; Willett, Wesley.; Prouzeau, Arnaud.; Anthes, Christoph.; B?schel, Wolfgang.; Dunne, Cody.; Dwyer, Tim.; Grubert, Jens.; Haga, Jason H.; Kirshenbaum, Nurit.; Kobayashi, Dylan.; Lin, Tica.; Olaosebikan, Monsurat.; Pointecker, Fabian.; Saffo, David.; Saquib, Nazmus.; Schmalstieg, Dieter.; Szafir, Danielle Albers.; Whitlock, Matt.; Yang, Yalong. (Tufts University. Tisch Library., 2023)
Keywords: Immersive analytics, augmented reality, data visualisation, grand research challenges, virtual reality.; Topic: Human-centered computing / Human computer interaction (HCI); Topic: Human-centered computing; ACM Open.